Hierarchically Ordered Nanoporous Carbon with Exclusively Surface‐Anchored Cobalt as Efficient Electrocatalyst. Issue 7 (9th June 2022) - Tang, Chaoyun; Ramírez‐Hernández, Maricely; Thomas, Belvin; Yeh, Yao‐Wen; Batson, Philip E.; Asefa, Tewodros
Abstract: A hierarchically ordered porous carbon electrocatalyst with exclusively surface‐anchored cobalt species, dubbed Co@HOPC, is synthesized from polyaniline and cobalt‐functionalized silica microparticles templates, and its high electrocatalytic activity for the oxygen evolution reaction (OER) is demonstrated. The material requires a small potential (320 mV) to drive the reaction with a current density of 10 mA cm −2 and a small Tafel slope of 31.2 mV dec −1 . Moreover, Co@HOPC shows better catalytic activity for OER than in situ cobalt‐doped and surface cobalt‐loaded hierarchically ordered porous carbon materials synthesized by traditional methods. This is due to the abundant surface cobalt species present in Co@HOPC and the material's good electrical conductivity. This work provides a new strategy to utilize functionalized silica microparticles as templates to synthesize hierarchically ordered porous carbon materials with metal‐rich surfaces and efficient electrocatalytic activities. Abstract : A hierarchically ordered nanoporous carbon with exclusively surface‐anchored single cobalt atoms, dubbed Co@HOPC, is synthesized from polyaniline and cobalt‐functionalized silica microparticles templates. The material shows a high electrocatalytic activity for the oxygen evolution reaction while remaining stable.